Lack of respect, role uncertainty and satisfaction with clinical practice among nursing students: the moderating role of supportive staff - Galletta, Maura; Portoghese, Igor; Aviles Gonzales, Cesar Ivan; Melis, Paola; Marcias, Gabriele; Campagna, Marcello; Minerba, Luigi; Sardu, Claudia (Acta Biomedica Atenei Parmensis, 2017)
Background and aims: Clinical learning placements provide a real-world context where nursing students can acquire clinical skills and the attitudes that are the hallmark of the nursing profession. Nonetheless, nursing students often report dissatisfaction with their clinical placements. The aim of this study was to test a model of the relationship between student’s perceived respect, role uncertainty, staff support, and satisfaction with clinical practice. Method: A cross-sectional, descriptive survey was completed by 278 second- and third-year undergraduate nursing students. Specifically, we tested the moderating role of supportive staff and the mediating role of role uncertainty. Results: We found that lack of respect was positively related to role uncertainty, and this relationship was moderated by supportive staff, especially at lower levels. Also, role uncertainty was a mediator of the relationship between lack of respect and internship satisfaction; lack of respect increased role uncertainty, which in turn was related to minor satisfaction with clinical practice. Conclusion: This study explored the experience of nursing students during their clinical learning placements. Unhealthy placement environments, characterized by lack of respect, trust, and support increase nursing students’ psychosocial risks, thus reducing their satisfaction with their clinical placements. Due to the current global nursing shortage, our results may have important implications for graduate recruitment, retention of young nurses, and professional progression.